Indonesian as a Unifying Language of the Nation - Chairunnisa Chairunnisa; Ahmad Ari Masyhuri; Syahidah Aulia (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to analyze Indonesian as a unifying language of the nation. Quantitative descriptive research method. Research subjects are selected from Universitas Pembangunan Nasional Veteran Jakarta students and Other Universities as many as 20 respondents. Subjects in this study are taken using a questionnaire distributed online via google form as many as 7 statements. The results show that students agreed with the statement that Indonesian as a national identity as well as a unifying language of the nation and Indonesian language must be preserved as long as the unitary state of the Republic of Indonesia is established.